Effectiveness of Slow Stroke Back Massage with Virgin Coconut Oil on Pressure Injury Risk - Fathul Maysarah Syahab; Taharuddin; Annaas Budi Setyawan (CV. CENDIKIA JENIUS INDONESIA, 2026)
Background: Stroke is a neurological condition that causes nerve paralysis. Patients with hemorrhagic stroke may require a surgical procedure in the form of a craniotomy, which results in limited mobility. This condition can lead to complications, one of which is skin breakdown that may develop into pressure injuries. One of the efforts to reduce the risk of pressure injuries is slow stroke back massage using virgin coconut oil . Objective: This study aimed to implement a slow stroke back massage intervention using virgin coconut oil to reduce the risk of pressure injuries in patients with hemorrhagic stroke. Methods: This study employed a case study design involving a hemorrhagic stroke patient in the ICU of RSUD Aji Muhammad Parikesit Tenggarong. The nursing intervention in the form of slow stroke back massage using virgin coconut oil was administered twice daily for four days. Results: The results showed an improvement in the Braden Score from 8 (very high risk of pressure injury) to 12 (high risk of pressure injury). Conclusion: Slow stroke back massage using virgin coconut oil plays an effective supportive therapy role in reducing the risk of pressure injuries in patients undergoing prolonged bed rest